2014
DOI: 10.1007/s00264-014-2436-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of external fixators for damage-control orthopaedics in natural disasters like the 2005 Pakistan earthquake

Abstract: Purpose In the 2005 Pakistan earthquake, the great many injured with multiple fractures and open wounds provided a unique opportunity to practice damage-control orthopaedics. External fixators remain a time-tested tools for operating surgeons on such occasions. The locally manufactured, readily available Naseer-Awais (NA) external fixator filled such needs of this disaster with good outcome. Methods This is a retrospective descriptive study of 19,700 patients that presented over seven months to the two centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…They noted that the use of external fixation and, when necessary, amputation, as a means of DCO allowed fractures to be definitively addressed later by more sufficiently staffed and supplied treatment teams or allowed patients to be transported to better-equipped facilities [ 22 ]. Awais et al noted similar findings, advocating for the use of both external fixation and, when necessary, amputation, after the 2005 earthquake in Pakistan, which claimed more than 73,000 lives [ 20 , 23 ]. A retrospective study after that earthquake reported that in 295 of 1145 fractures (26%), reductions were achieved with external fixation [ 20 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They noted that the use of external fixation and, when necessary, amputation, as a means of DCO allowed fractures to be definitively addressed later by more sufficiently staffed and supplied treatment teams or allowed patients to be transported to better-equipped facilities [ 22 ]. Awais et al noted similar findings, advocating for the use of both external fixation and, when necessary, amputation, after the 2005 earthquake in Pakistan, which claimed more than 73,000 lives [ 20 , 23 ]. A retrospective study after that earthquake reported that in 295 of 1145 fractures (26%), reductions were achieved with external fixation [ 20 ].…”
Section: Discussionmentioning
confidence: 83%
“…The focus should be on hemorrhage management, wound debridement, infection control, and soft tissue stabilization. External fixation is key to proper management of fractures and soft tissue stabilization, yielding favorable results in earthquake disaster scenarios [ 20 22 ]. The ratio of external fixation to ORIF depends largely on when the response team arrives at the earthquake location [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the fractures are open (61.4%). According to the principle of damage control orthopaedic surgery, skeletal stabiliation was initially achieved by external fixation (18%) 17. Later internal fixation will be performed in Role 3 Hospital 18.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, external fixation may be the more appropriate choice of intervention over internal fixation, especially in natural disaster and conflict settings. In this way, even in those settings where the minimum requirements for a procedure like internal fixation do not exist, a high proportion of the trauma caseload may be able to be managed when a procedure like external fixation is possible [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%